2022
DOI: 10.1155/2022/4313549
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Fuzzy Comprehensive Evaluation Random Matrix Model for the Assessment of Foreign Language Translation Level in Universities

Abstract: In this paper, the random matrix method of a fuzzy comprehensive evaluation is used to conduct in-depth research and analysis on the assessment of foreign language translation levels in universities, and the corresponding model is designed for the automatic assessment of translation levels in university education. The Hessian matrix of the second-order optimization method is used to analyze the geometric properties of the loss plane of the deep neural network, and it is proved that the Hessian matrix can be co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Xie and Wu [21] have suggested that in-depth research and an examination of the standards for translating foreign languages in universities be done using the fuzzy comprehensive evaluation approach of random matrix, and that a corresponding model be developed for the automatic assessment of university education 's translation proficiency. The geometric properties of the deep neural network's loss plane were investigated using the second-order optimization method's Hessian matrix.…”
Section: Methodsmentioning
confidence: 99%
“…Xie and Wu [21] have suggested that in-depth research and an examination of the standards for translating foreign languages in universities be done using the fuzzy comprehensive evaluation approach of random matrix, and that a corresponding model be developed for the automatic assessment of university education 's translation proficiency. The geometric properties of the deep neural network's loss plane were investigated using the second-order optimization method's Hessian matrix.…”
Section: Methodsmentioning
confidence: 99%